The box: oxford literacy web - Graham, Elspeth; Newsham, Ian (Oxford University Press Karachi, 1999)
Part of The Oxford Literacy Web, a literacy programme designed to guide schools through the primary years, this title features stories, events, and illustrations to talk about early school experiences. It shows what Mrs Best's reception class likes doing and allows you to find out more about Cheep, the baby bird. It also features Buzz and Josh.